Refrains for Moving Bodies : Experience and Experiment in Affective Spaces - McCormack, Derek P. (Book collections on Project MUSE., 2013)
Putting the work of Henri Lefebvre, William James, and John Dewey in conversation with dance theorists, Derek P. McCormack reflects on how bodies both move in and generate affective spaces.